Magnetic Fluids and their Applications - Jozef Kudelcik; Maria Kudelcikova (Communications - Scientific letters of the University of Zilina, 2018)
Magnetic fluids contain magnetic nanoparticles which are dispersed in water or various types of oils. Magnetic nanoparticles are monodomain and their magnetic moments are oriented in the direction of the magnetic field. They interact with each other and create new structures, which depend on parameters of magnetic nanoparticles, temperature, values, and development of magnetic and electric fields. This paper describes two basic methods of investigation of magnetic fluids in magnetic and electric fields by the acoustic and the dielectric spectroscopy. Magnetic fluids have wide application in technology, medicine and other areas